Physical forces driving chlorophyll-a variability in the South Java Sea Shelf: a spatio-temporal analysis. Issue 1 (October 2021) - Budiman, A S; Bengen, D G; Arifin, Z; Nurjaya, I W; Ismail, M F A
Abstract: The wind and current are two physical forces that strongly influence the biogeochemistry in coastal waters. Both of these forces could enhance the Chlorophyll-a (Chl-a) concentration through the upwelling process. Here we examine the contribution of the wind and current to the Chl-a variability in the South Java upwelling system in terms of wind stress and bottom stress respectively using satellite-derived and reanalysis data from 2002 to 2017. Ten longitudinally cells were used for further analysis. A long-term Chl-a shows a strong longitudinal gradient of Chl-a with the highest value on the shelf. Seasonal and Inter-annual Chl-a analysis shows the evidence of the monsoonal winds and other forcing effects relevant to the previous studies. Wind stress ( τwx ) has a strong seasonal variation which is upwelling- favorable during southeast monsoon coincide with higher Chl-a suggesting wind as the main forces during that time, while bottom stress ( τbx ) has more complicated variations, but it's seen that τwx mostly downwelling-favorable or eastward circulations. There were about 39.92- 52.94% of positive Chl anomalous events generated by the combination of upwelling- favourable τwx and downwelling-favorable τbx, higher than other combinations. In terms of Oceanographic drivers, the wind has a higher effect on enhancing Chl-a through a negative correlation. τwx leads the Chl-a anomalies by about 15 – 24 days with a correlation coefficient of more than 0.6.